The Effect of Self-Efficacy, Interpersonal Communication and Work Ethics on Sustainable Work Commitment - Indriyaningrum, Kis; Fauzan, Mohammad (Universitas Pamulang, 2023)
The objectives of the study were to test and analyze (1) the effect of self-efficacy on sustainable work commitments, (2) the influence of interpersonal communication on sustainable work commitments, (3) the influence of work ethics on sustainable work commitments. This type of research is explanatory research. The research population was all employees of Honda Surya Utama Perkasa Semarang Dealership as many as 123 employees. Instruments used in data collection using questionnaires with Likert scale Analysis techniques using regression models. Research findings that Self-Efficacy positively affects sustainable work commitments. Interpersonal Communication has no effect on continuous work commitment. Work Ethic positively affects the commitment to sustainable work. The implications of the findings of this study show that employees' sustainable work commitment is determined by employee self-efficacy and work ethic. Therefore, leaders in recruiting employees need to assess the ownership aspects of self-efficacy and work ethics.